Implementasi Program Keterampilan Sosial di Panti Asuhan Cinta Kasih Sei Brantas Medan Sunggal - Sembiring, Delvia Laura; Ritonga, Fajar Utama (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Social Skills Program refers to an individual’s ability to interact, communicate, and build positive relationships with others. These skills are essential in shaping personality, expanding social networks, and supporting everyday social life. This program aims to provide training and development for children living in orphanages so that they acquire adequate skills to interact with others, which will support their social development in the future. This research was conducted at the Cinta Kasih Orphanage Sei Brantas, Medan Sunggal. The research method used is Descriptive Qualitative. The key informant in this study is the Head of the Cinta Kasih Orphanage Sei Brantas. The main informants consist of four children living in the orphanage. Additionally, there is one supporting informant, a member of the community who has knowledge of the Social Skills Program at the orphanage. Data collection techniques include observation, interviews, documentation, and literature study. The data obtained was analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the Social Skills Program at the Cinta Kasih Orphanage Sei Brantas, Medan Sunggal has been successfully implemented. This is evident from the fulfillment of all three indicators: program elements, implementing organization elements, and beneficiary elements, in accordance with David C. Korten’s theory on successful program implementation.